Emerging Technologies for Genome-Wide Profiling of DNA Breakage - Rybin, Matthew J.; Ramic, Melina; Ricciardi, Natalie R.; Kapranov, Philipp; Wahlestedt, Claes; Zeier, Zane (Frontiers in Genetics, 2021)
Genome instability is associated with myriad human diseases and is a well-known feature of both cancer and neurodegenerative disease. Until recently, the ability to assess DNA damage—the principal driver of genome instability—was limited to relatively imprecise methods or restricted to studying predefined genomic regions. Recently, new techniques for detecting DNA double strand breaks (DSBs) and single strand breaks (SSBs) with next-generation sequencing on a genome-wide scale with single nucleotide resolution have emerged. With these new tools, efforts are underway to define the “breakome” in normal aging and disease. Here, we compare the relative strengths and weaknesses of these technologies and their potential application to studying neurodegenerative diseases.